Pembangunan Ekonomi Islam dalam Perspektif Maqashid Syari’ah - Kartika Rose Rachmadi; Kasuwi Saiban; Misbahul Munir (Universitas Islam Malang, 2021)
The economic development of the people is a big problem faced by people today, and indeed The solution can only be done by Muslims himself by returning to Allah's rules, in among others by: instilling entrepreneurial traits for each individual people, build strong partnerships/networks with various parties, especially with fellow Muslims, make policies that are more pro-economic growth of the people, by supporting morally and materially sourced from zakat funds, carry out transactions and economic behavior in accordance with the rules of Islamic teachings.